Cardiovascular Health School Program (PESCA). Methodology and initial results: 2018-2020 - Zárate Osuna, Fernando; Zapico, Augusto G; Martín Carpi, Francisco Javier; Ramón Krauel, Marta; González Gross, Marcela (Nutrición hospitalaria : organo oficial de la Sociedad Española de Nutrición Parenteral y Enteral, 2021)
Introduction: despite the fact that 40 % of children in Spain, ages 6 to 9, are overweight or obese, and 2/3 of them are at risk of developing cardiovascular disease, there is a lack of protocolized efficient interventions to fight this important health problem. The PESCA project aims to reduce the prevalence of overweight and obesity with a transversal model focused on a school intervention, but also involving families and primary care doctors, to increase the quantity and quality of physical activity (PA) and improve eating habits. Methods: a 5-step protocol was carried out at schools: 1) family and personal background questionnaire for children; 2) body mass index (BMI); 3) bioimpedance corporal composition (BIA); 4) hand grip dynamometry (DIN); and 5) medical physical examination. As a result, each subject received a medical report about his/her diagnosis of body weight and composition and cardiovascular health, and also recommendations to improve eating habits and increase physical activity. Results: in the first two years of PESCA, the weekly time of physical activity has significantly increased among participants (up to 20.12 %; p < 0.001). In addition, the prevalence of overweight/obesity has significantly declined in both girls and children under 6 years of age (35.78 % and 58.92 %; p < 0.05, respectively). Conclusion: the school, pediatrician, and family working together on a transversal intervention has shown effectiveness in reducing the lack of diagnosis and prevalence of overweight and obesity in children.